2013
DOI: 10.4161/cc.23285
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage causes TP53-dependent coupling of self-renewal and senescence pathways in embryonal carcinoma cells

Abstract: Recent studies have highlighted an apparently paradoxical link between self-renewal and senescence triggered by DNA damage in certain cell types. In addition, the finding that TP53 can suppress senescence has caused a re-evaluation of its functional role in regulating these outcomes. To investigate these phenomena and their relationship to pluripotency and senescence, we examined the response of the TP53-competent embryonal carcinoma (EC) cell line PA-1 to etoposide-induced DNA damage. Nuclear POU5F1/OCT4A and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 43 publications
(53 reference statements)
7
49
0
Order By: Relevance
“…Markers of accelerated senescence and DNA damage were unexpectedly found to be linked to markers of stemness in senescing IMR-90 fibroblasts [56] and etoposide-or irradiation treated tumour cells arrested in G2-phase [57, 58]. The p21-dependent senescence related to stemness pathways (TGF-β and PI3K) was revealed in normal embryogenesis [79].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Markers of accelerated senescence and DNA damage were unexpectedly found to be linked to markers of stemness in senescing IMR-90 fibroblasts [56] and etoposide-or irradiation treated tumour cells arrested in G2-phase [57, 58]. The p21-dependent senescence related to stemness pathways (TGF-β and PI3K) was revealed in normal embryogenesis [79].…”
mentioning
confidence: 99%
“…Interestingly, our recent research on etoposide-treated embryonal carcinoma cells showed that a potential regulator and trigger for this switch is OCT4 (POU5F1), a carrier of life-cycle totipotency [82]; and induced in a TP53-dependent manner alongside p21CIP1. The choice between the two opposite cell fates (reinitiate cell divisions or undergo terminal senescence) in transiently bi-potential cells is undertaken in G2 arrest [57] and this barrier can become adapted to start polyploidy [56]. When the tetraploidy barrier is overcome, the TP53 tumour-suppressing function becomes surpassed [83], likely by methylation of its promoter [84], while mTOR linking to p21-mediated senescence becomes suppressed, thus allowing the reversal of senescence [58].…”
mentioning
confidence: 99%
“…The most surprising fact was that regulators of the opposing processes of senescence (p21CIP1) and self-renewal OCT4A (POU5F1) were highly induced in the same G2-arrested cells (Figures 2C and 4A). This was downstream of activated TP53, as both p21 and partly OCT4A became downregulated after TP53 RNAi silencing ( Figure 2C) [45]. Further study [46] revealed that p53-activated OCT4A down-regulated p21CIP1, moderating its expression and preventing cells from precipitating terminal senescence or apoptosis (Figure 2D), thus providing the opportunity for repair.…”
Section: Ovarian Germline Cells Challenged By Genotoxic Stress Displamentioning
confidence: 99%
“…P53 is activated and simultaneously induces p21CIP1 and OCT4A. OCT4A moderates the expression of p21CIP1 preventing apoptosis or terminal senescence [45,46]. Activated p53 also downregulates the promoter of Nanog gene [49].…”
Section: Transient Bi-potentiality Of Csc For Senescence and Self-renmentioning
confidence: 99%
See 1 more Smart Citation